Antioxidant activity evaluation of NSIC Rc216 (Oryza sativa) variety's bran and germ layers - Tornalejo, Norielle Marie B.
Rice (Oryza sativa) is one of the main cereal crops, as well as staple food for most of the world?s population. Rice by-products such as rice bran and rice germ are two of the extensively abundant agricultural wastes from the rice industry. In this study, the antioxidant activity of a local rice variety in the Philippines, NSIC Rc216?s bran and germ methanolic extracts were evaluated. The order of antioxidant activity was evaluated by measurement of total phenolic content, reducing power and scavenging capacity on DPPH radical. The TPC of the rice bran (4.91±0.04 mg/g) was significantly (p < 0.05) higher than rice germ (1.99±0.05 mg/g). The standard ascorbic acid has the greatest reducing power followed by the rice germ and rice bran extracts. In the DPPH assay, ascorbic acid has the highest EC50 of 12.23 µg/mL while the rice bran and rice germ have 44.44 µg/mL and 25.94 µg/mL EC50 values, respectively. The rice germ extracts produced stronger results than bran extracts with reducing power and DPPH free radical scavenging activity. These results indicated that the methanolic rice bran and germ extracts of NSIC Rc216 variety might potentially be natural sources of antioxidants.